Preservação digital: um estudo de caso sobre o jogo “A Revolta da Cabanagem” - PANTOJA, Davison de Oliveira (2023)
The research identified the potentialities and weaknesses of digital preservation connected to the game "The Revolt of the Cabanagem", title this produced in the period from 2006 to 2009 by the Virtual Reality Laboratory (LARV), connected to Faculty of Computer Engineering and Telecommunications (FCT) of the Federal University of Pará (UFPA). The work is justified in presenting data on a pioneering game in the northern region which deals with the history of Cabanagem (revolt occurred in Pará between 1835 and 1840), through playful aspects for educational purposes. Initially, the research presents a brief historical contextualization about the origin of video games, followed by an analysis relating these supports with Archivology, considering them as potential archival documents, and a brief description about the game "The Revolt of the Cabanagem". The methodology, based on a case study, verified the types of files that were used for the creation of the game, as the data storage is being carried out, identifying intrinsic and extrinsic characteristics and whether there are digital preservation strategies for the title, taking advantage of interviews with the game's developers in different media. The research identified that, although much of the features of the title are available, the game has weaknesses that partially impair its gameplay, being also verified difficulty for its download and considerable total loss of your informational record, due to the absence of the developers in maintaining the game. However, the research identifies potential for expansion of analysis to other titles related to the digital preservation of electronic games in Pará.